2014
DOI: 10.1371/journal.pone.0109178
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing to Decipher the Genetic Heterogeneity of Hearing Loss in a Chinese Family with Deaf by Deaf Mating

Abstract: Inherited deafness has been shown to have high genetic heterogeneity. For many decades, linkage analysis and candidate gene approaches have been the main tools to elucidate the genetics of hearing loss. However, this associated study design is costly, time-consuming, and unsuitable for small families. This is mainly due to the inadequate numbers of available affected individuals, locus heterogeneity, and assortative mating. Exome sequencing has now become technically feasible and a cost-effective method for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
(39 reference statements)
0
11
0
1
Order By: Relevance
“…Moreover, they have opportunity to meet in hospitals, patient supporting groups or specialized schools. This could explain association of distinct genetic diseases of the same/different group but also the cases of compound heterozygotes (12). Comorbidity due to homogamy, although not yet reported in the Tunisian population, has to be kept in mind.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, they have opportunity to meet in hospitals, patient supporting groups or specialized schools. This could explain association of distinct genetic diseases of the same/different group but also the cases of compound heterozygotes (12). Comorbidity due to homogamy, although not yet reported in the Tunisian population, has to be kept in mind.…”
Section: Discussionmentioning
confidence: 97%
“…Two of the case reports used comprehensive genetic testing for diagnosis of families with and found both non-syndromic and syndromic forms of hearing loss segregating simultaneously 22,23 . Two studies identified families with three forms of hearing loss segregating simultaneously 23,24 . And one study identified a possibly life threatening disorder, Long QT syndrome caused by a mutation in KCNQ1 , with exome sequencing, in a patient with what appeared to be non-syndromic hearing loss 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The primary advantage of NGS over Sanger method is the inexpensive production of large amounts of sequencing data [ 3 ]. With unprecedented high throughput, highly parallel and base-pair resolution data of NGS, whole-exome sequencing (WES) and whole-genome sequencing (WGS) are all applied in the diagnostic testing or carrier screening of Mendelian genetic disorders [ 4 7 ]. WGS and WES yield myriad of genetic variations which have an advantage in carrier screening.…”
Section: Introductionmentioning
confidence: 99%